Ultra-low frequency transcutaneous electric nerve stimulation does not affect the centric relation registration. Issue 1 (2nd January 2018) - de Bragança, Rafaella Mariana Fontes; Rodrigues, Carolina Almeida; Melchior, Melissa Oliveira; Magri, Laís Valencise; Mazzetto, Marcelo Oliveira
Abstract: Objective: To evaluate the influence of ULF-TENS on the displacement of the mandibular condyle and on the repeatability of centric relation (CR) registration of three different techniques: bimanual manipulation (BM), long strip technique, and harmonic centric occlusal relationship (R.O.C.A. wires). Methods: Twenty-five participants without temporomandibular disorder (TMD) underwent two study stages conducted via electronic position analysis: (1) three CR records were made, one for each manipulation technique; (2) the ULF-TENS was applied for 30 min, and after that the same CR records were repeated. Statistical analyses: Mann–Whitney, ICC, and one-tailed F test. Results : The ULF-TENS did not influence the condyle total displacement, regardless of CR recording technique used ( p  > 0.05). BM showed an improvement in repeatability after ULF-TENS. Discussion: Concerning the variance, BM showed less variation at the X -axis. Long strip technique and R.O.C.A. wires varied less at the Y -axis. Long strip technique was again less variable at the Z -axis.